Knowledge of HIV and benefits of male medical circumcision amongst clients in an urban area - Abidemi Faleye (AOSIS, 2014)
Background: Male medical circumcision (MMC) has been shown to reduce the risk of HIV transmission in circumcised men by up to 60%. Following recommendations from the World Health Organization, South Africa adopted MMC as a preventative strategy against HIV in 2010 and set up circumcision camps across the country. Concerns have been raised about condom avoidance following MMC because of a mistaken belief about the benefits of MMC. Aim and setting: The aim of this study was to describe the profile and knowledge about HIV and circumcision amongst men presenting for MMC in an urban area in KwaZulu-Natal. Methods: This was a cross-sectional descriptive study of 394 clients over the age of 18 years who presented to two MMC sites in Durban between November 2012 and March 2013. A validated questionnaire was used to collect data. Results: The mean age of clients presenting for MMC was 28 years. Most clients were black, single, unemployed and sexually active. The majority presented for MMC because they believed that MMC would reduce their risk of acquiring HIV infection. Knowledge about HIV transmission was very good and 86.3% of clients were aware that risky sexual behaviour suchas condom avoidance could reverse the benefits of MMC. Conclusion: The knowledge of HIV and benefits of MMC was very good amongst those presenting for MMC. However as MMC is primarily a preventative strategy, innovative methods to promote MMC prior to first sexual encounter need to be explored. Further research is needed to determine whether the benefits of MMC on the reduction of HIV transmission aresustained in routine practice.   [Full text article to follow]